Sistema de integração de tecnologias de agregação de medição : uma abordagem baseada em modelos - Silva, Eduardo Fontana Vieira e (2004)
The support to the activities of a company requests the collaboration among the several computation systems that it possesses. Thus, several organizations have been uniting efforts in the sense of establishing patterns, architectures and formats of representation of data that allow the interoperability among the systems of a company and even among companies. Some common characteristics can be observed among the several initiatives. One of them is that, more and more, the integration of heterogeneous systems is being treated as a question of "understanding" among those systems. These proposals lead to an approach that privileges the understanding of the information being shared, through the use of logical models of information. Another point has been the incorporation of concepts of the software paradigm known as Object Orientation. This technology allows the construction of models of devices through from the composition of basic functional blocks. This work presents a proposal for integration of heterogeneous devices in the context of Electronic Meters of Electric Energy. With an approach based in the construction of models that describe the domain of the measurement problem, we show the possibility of integrating different models of meters in one configuration and metering system. The developed prototype has validated the techniques and methodology employed.